The Effectiveness of Cognitive Behavioral Counseling with a Self-Management Technique to Reduce Students Smartphone Addiction and Phubbing - Kamil, Ahmad; Sutoyo, Anwar; Purwanto, Edy (Universitas Negeri Semarang, 2023)
Smartphone is a form of technological and information advancement which now has become a necessity in life. However, excessive use of a smartphone makes its users susceptible to addictive behavior and phubbing. Regarding this issue, the present study strived for testing the effectiveness of cognitive behavioral group counseling with a self-management technique to reduce smartphone addiction and phubbing in students at SMA Negeri 12 Enrekang. It used an experimental method with a pretest-posttest control group design and involved 12 students with high levels of smartphone addiction and phubbing as the subjects. Based on the Mixed ANOVA test, the intervention applied could reduce smartphone addiction and phubbing in grade twelve students at SMA Negeri 12 Enrekang. Further discussion regarding the implications and limitations are presented in the discussion chapter.